Improving Students' Social Activity Skills and implementing it in Practice - Avazbekovna, Ergasheva Maftunakhon (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
This article provides detailed information about the development of social activity skills among students studying in higher education institutions based on historical knowledge, social activity skills and their components in their development as mature individuals.